A ISO 26.000 E O CONSENSO NORMATIVO SOBRE A RESPONSABILIDADE SOCIAL EMPRESARIAL - Lima, Luciana Cristina da Conceição (2013)
The objective of this research is to build an assessment of the potential applications of ISO 26000, on the question to which it turns, that it is the social responsibility across the organizations. For the development of this study, exploratory methodology and literature review were used with a qualitative approach, in order to demonstrate the various concepts of Corporate Social Responsibility - CSR and the outbreak of regulatory initiatives on the theme. From the analysis of the reflections of many authors on the subject, the difficulties in reaching a consensus on CSR actions were pointed out, due to the great diversity of interests, cultures, politics, economics and development. It is a fact that there is a global movement about the standardization of procedures that encompass social responsibility. These initiatives, with its requirements, aim to assist organizations in general on the adoption of practices that enable the development of a behavior, focusing at the social responsibility management and therefore providing a contribution to a more sustainable development, taking into account the environmental, economic and social aspects. However, the present study aims to verify the commonalities and differences between the regulatory initiatives on social responsibility. The proposal was to compare these standards with the latest CSR initiative in the world, that is the ISO 26000 - International Standard on Social Responsibility and analyze its main formative aspects and objectives. This analysis will enable the understanding of the current situation of standards and the real prospects for standardization on a global scale, from the consensus on social responsibility.